2017
DOI: 10.1161/circep.116.004778
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Preexcitation and Risk of Cardiovascular Morbidity and Mortality

Abstract: Background— The majority of available data on the clinical course of patients with ventricular preexcitation in the ECG originates from tertiary centers. We aimed to investigate long-term outcomes in individuals from a primary care population with electrocardiographic preexcitation. Methods and Results— Digital ECGs from 328 638 primary care patients were collected during 2001 to 2011. We identified 310 individuals with preexcitation (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
(25 reference statements)
2
23
0
Order By: Relevance
“…At an older age, symptoms can be more serious, such as presyncope and syncope [13]. SVTs are generally not life-threatening, but some specific situations (in patients with WPW syndrome and AF or after atrial switch operation) can cause sudden cardiac death [14, 15].…”
Section: Clinical Findings and Initial Evaluationmentioning
confidence: 99%
“…At an older age, symptoms can be more serious, such as presyncope and syncope [13]. SVTs are generally not life-threatening, but some specific situations (in patients with WPW syndrome and AF or after atrial switch operation) can cause sudden cardiac death [14, 15].…”
Section: Clinical Findings and Initial Evaluationmentioning
confidence: 99%
“…ECG changes can be found in different stages of COPD and can be associated with the increased death risk. An increased burden of cardiac arrhythmias has also been recognized recently [5]. In COPD, various mechanisms can influence ECG diversely, independent of a possibly CAD [6].…”
Section: Introductionmentioning
confidence: 99%
“…Along with pulmonary involvement, there are significant extra pulmonary effects in COPD [3,4,5]. COPD can influence electrocardiographic (ECG) changes variously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients aged 65 years or older had a significantly higher risk of death (HR, 1.85) when compared with patients without preexcitation. 23 Stec et al 24 reported a case series of patients with asymptomatic preexcitation with dyspnea and exercise intolerance. No organic disease in the cardiopulmonary system was found.…”
mentioning
confidence: 99%